Legal Protection for the Recipient of the Franchise of "MAKJON" Pioneer of Martabak Japan" - Ayu Citra Santyaningtyas; Kukuh Budi Mulya; Gemilang Kirana (Rechtsvinding, 2026)
The franchise agreement raises a problem, this is a default committed by the franchisor due to the change of employees at the head office, the central franchisor begins to give a slow response until finally ignoring the message of the franchisee. This action hinders the sales process, due to the depletion of raw material inventory. The research method used is normative juridical research using legislative and conceptual approaches. The results of this research are a form of legal protection for franchisees when there is a default in Government Regulation number 42 of 2007 and Regulation of the Minister of Trade number 71 of 2019, namely there is a clause regarding the rights and obligations of the parties to settlement efforts that can be carried out by the franchisee, namely using the principle of out-of-court dispute resolution or non-litigation settlement. By way of deliberation to reach consensus or mediate. If the dispute resolution outside the court cannot be successful, then the parties can carry out the dispute resolution process through the court.